Bovine vitreous gel can reactivate replicative senescence of human dermal fibroblast - Maria Vianny Sansan; Sunardi Radiono; Muhamad Eko Irawanto; Yohanes Widodo Wirohadidjojo (Indonesian Journal of Biotechnology, 2018)
The most influential factor in the poor healing of chronic ulcers is replicative senescence of fibroblasts that are unresponsive to TGF-β1 stimulation. Cellular replicative senescence can be induced by cultivating normal human dermal fibroblasts (HDFs) in a serum-starved medium. In addition, increasing microenviroment mechanical forces by hyaluronic acid can ameliorate the TGF-β1 signaling of these senescent cells. One of natural resources of hyaluronic acid is bovine vitreous gel. In order to evaluate the effect of bovine-vitreous gel on replicative senescence of fibroblasts, we used various levels of bovine vitreous gel diluted in Dulbecco’s modified Eagle’s medium to stimulate cellular activities of serum-starved HDFs. Those cellular activities were compared to the control media, standardized hyaluronic acid, and to normal HDFs. Our results show that replicative senescence of HDFs treated with 50% bovine vitreous gel exhibited a significantly higher proliferation index, migration rate, and collagen deposition than those cultured in control media, and they displayed an equal level of cellular activity with the HDFs exposed only to standardized hyaluronic acid. We concluded that bovine vitreous gel can be used to stimulate replicative senescence of HDFs and therefore a potential candidate material to stimulate healing of chronic ulcers.